Consumption of sugar-sweetened beverages among International Islamic University Malaysia (IIUM), Kuantan students - Zahari, Nor 'Afifah; Hamirudin, Aliza Haslinda; Badarudin, Noor Ezailina (IIUM Press, 2018)
Introduction: Malaysian is one of the highest sugar consumers in the Asia Pacific region. There has been no available report quantifying sugar intake among Malaysian until Malaysian Adult Nutrition Survey (MANS) 2003 study was done. However, data concerning sugar consumption among university students is scarce. Objective/aim: This study was conducted to assess sugar sweetened beverages intake among International Islamic University Malaysia (IIUM) Kuantan students. Methodology: A total of 42 of IIUM Kuantan students was recruited by convenience sampling method. A questionnaire consisting of 3 days food record was distributed to all participants as a tool for data collection. Food record was analyzed using the Nutritionist Pro software prior to statistical analysis with SPSS version 12.0. P value was set as p<0.05 as statistically significant level. Results: The mean energy intake of the students is 1631 + 466 kcal/day, which is lower than the Recommended Nutrient Intakes (RNI) for Malaysian. The mean energy intake for male is 2197 ± 300 kcal/day and; while 1405 ± 295 kcal/day for female. The mean percentage of sugar intake from sugar-sweetened beverages in this population is 7.18%. A higher sugar-sweetened beverages consumption is found at breakfast, lunch and dinner compared to other meals. Conclusion and implication: Sugar intake from sugar sweetened beverages among the IIUM Kuantan students did not exceed the standard guidelines. Hence, this population is not at risk of adverse effects from excessive sugar intake which lead to lower risk of developing non-communicable disease.